An appraisal of TBM performances in Turkey in difficult ground conditions and some recommendations. (August 2016) - Bilgin, Nuh
Highlights: Difficulties of excavating with TBM in difficult ground conditions in Turkey are emphasized for 10 different tunnels. The effects of East and North Anatolian Faults on TBM performance are discussed. Geophysical studies are advised to be carried out in Istanbul Geology to detect ancient water wells. Abstract: The geology of Turkey is very complex and major Northern and Eastern Faults including minor faults associated to these faults create tremendous problems, like squeezing of the TBM, excessive water ingress, TBM face collapses, as encountered in the Kargi power tunnel, the Dogancay energy tunnel, the Gerede water tunnel, and the Nur Dagi railway tunnel. Mixed ground conditions with ophiolites, graphitic schists and melanges with boulders are other fundamental difficulties leading to squeezing and blocking of the TBMs or even causing complete failures of the segments and abandoning of the tunnel. A typical example for tunnel abandoning is the Kosekoy high speed tunnel and an example for excessive TBM squeezing is the Uluabat energy tunnel. The affects of dykes in the Istanbul region is known well by practicing tunnel engineers. These andesitic rocks, make fractures in the country rock and cause several problems during TBM excavation like blocking the cutterhead and excessive disc cutter consumption. Typical examples are the Goztepe-Kadıkoy Metro tunnels, and the Melen water tunnel. The Beykoz utility tunnel is one of the most difficult tunnelling projects in Istanbul. Presence of clay minerals existing within the geologic formations is also one of the main reasons clogging the cutterhead of TBM as encountered in the Suruc water project. The effects of complex geology on the excavation efficiencies of different type of TBM's used in the ten projects mentioned above are explained in this paper and some recommendations with a ground classification system for proper use of TBMs in faultyzones are given.